Drying peppercorn characteristics in fluidized bed dryer equipped with baffle vortex generators - V Chuwattanakul; K Banthumporn; P Promvonge; S Eiamsa-ard (My University, 2018)
The paper deals with the characteristic study of drying peppercorn using fluidized-bed dryer fitted with baffle vortex generators. The experiments were operated at three different superficial air velocities of 1.2Umf, 1.4Umf and 1.6Umf. Experiments were operated from the initial to final moisture contents of around 12% (dry basis). During the experiments, peppercorns were sampling every 5 minutes, for moisture analysis. A typical fluidized-bed dryer was also tested under similar operating conditions for the assessment. The results indicate that the influence of superficial air velocity on drying peppercorn characteristic in the fluidized-bed dryer fitted with baffle vortex generators is more significant than that in the typical fluidized-bed dryer. It is observed that fluidized-bed dryer fitted with baffle vortex generators shows better performance in reducing moisture content with faster drying rate than the typical fluidized bed dryer especially at high superficial air velocity due to the strong longitudinal vortex which helps in improving the fluid mixing, heat and mass transfer rates.
Keywords: Baffle; Air velocity; Food Drying and Modeling